The academic self-efficacy scale in mathematics using Confirmatory Factor Analysis (CFA) - Mulin Nu'man; Dwi Amalia Putri; Fina Durrotun Nafisah (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
The development of an academic self-efficacy instrument is considered necessary for one's ability to manage and complete a series of actions required to accomplish a task. This study aims to develop and test the validity and reliability of the self-efficacy instrument, specifically the Academic Self-Efficacy Questionnaire, comprising 15 items across three dimensions, each with five indicators. The research method in this study involved developing an instrument in six stages. Participation in this study consisted of 203 junior high school and Madrasah Tsanawiyah (MTs) students. Participation was spread across 51 students (25.1%) in Grade VII, 100 students (49.3%) in Grade VIII, and 52 students (25.6%) in Grade IX.  Based on the analysis results, it was found that the 15 items developed were fit because they met eight model fit criteria, including Chi-square = 90.45 < 2df (df = 79),  p-value = 0.17802 ( ≥ 0.05), RMSEA= 0.027  (≤ 0.05), NFI = 0.99 (≥ 0.9), CFI = 1 (≥ 0.9), IFI = 1 (≥ 0.9), GFI = 0.94 (≥ 0.9), AGFI = 0.91 (≥ 0.9), PGFI = 0.62 (≥ 0.6), NNFI = 1.00 (≥ 0.9). Thus, the questionnaire developed is in accordance with the planned dimensions, which reflect the variable of self-efficacy in a valid, reliable, and significant manner, supported by behavioural indicators for each dimension. Therefore, this instrument can be used for further measurement.